2014
DOI: 10.1080/02614367.2014.923492
|View full text |Cite
|
Sign up to set email alerts
|

Older adults’ lifelong embodied experiences of leisure time aquatic physical activity in the United Kingdom

Abstract: Aquatic physical activity has considerable benefits for older adults. However, participation rates remain low in the United Kingdom (UK). Recognition of the importance of embodied and narrative elements of ageing has increased in recent times. Old age is considered a life stage interdependent with other, earlier life stages, rather than as a distinct period. This study uses a figurational perspective to investigate older adults’ changing perceptions and embodied experiences of aquatic activity throughout their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The accounts posted on blogs can thus help us obtain valuable narratives of the personal experience that has marked runners [ 62 , 63 ], as a participatory sense-making process emerges from the interaction between the teller and the reader [ 64 ]. Sport sciences have also shown great interest in these narratives in the fields of health (e.g., [ 65 ]), physical activity and leisure [ 66 ], physical education (e.g., [ 67 ]), adapted physical activity [ 68 ] and elite sport (e.g., [ 69 ]).…”
Section: Methodsmentioning
confidence: 99%
“…The accounts posted on blogs can thus help us obtain valuable narratives of the personal experience that has marked runners [ 62 , 63 ], as a participatory sense-making process emerges from the interaction between the teller and the reader [ 64 ]. Sport sciences have also shown great interest in these narratives in the fields of health (e.g., [ 65 ]), physical activity and leisure [ 66 ], physical education (e.g., [ 67 ]), adapted physical activity [ 68 ] and elite sport (e.g., [ 69 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Such spaces were considered to offer specific threats to their child’s embodied integrity. Changing areas are often considered transitory spaces within which ‘inside’ and ‘outside’ routines, behaviours and also physical matter mix and blend, sometimes dangerously (Evans and Allen-Collinson, 2014; Evans and Sleap, 2015; Fusco, 2006). In these spaces, outdoor ‘everyday’ clothing is shed, and bodies are transformed into ‘swimming’ bodies through techniques of performative regulation and tacit etiquette.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been highlighted how within such a configuration of power relationships, swimming bodies begin to self-regulate such that they become the ‘principal of their own subjection’ (Foucault, 1979: 172), even when, as when monitoring ‘excess’ weight in elite swimming, some of the practices are unhealthy and damaging to wellbeing (McMahon and Penney, 2013). Furthermore, studies have identified how embodied experiences of aquatic activity are influenced by expectations regarding hygiene, health and fitness (Evans and Allen-Collinson, 2014; Evans and Sleap, 2015), and that some aquatic activities, including aqua aerobics and ‘parent–toddler’ sessions, are often associated specifically with women’s body projects (Evans and Sleap, 2012, 2013, 2015). These studies bring the centrality of the swimming body in gendered and gendering practices to the fore.…”
Section: Introductionmentioning
confidence: 99%
“…Their experiences show that defining physical activity simply by single bouts of exercise at predetermined levels of intensity is likely to prioritize the public health outcomes of physical activity for older people at the expense of wider impacts including on well-being, social connection, and friendship. Following Evans and Sleap ( 2015 ) our work reflects the idea that old age is one of many life stages all of which are interdependent with one another. It is not just the passage of time that marks out the aging process.…”
Section: Strategy and Methods For Coproduction In The Health And Sport Engagement Projectmentioning
confidence: 99%